A Cost Effective Experimental Emulator for Fuel Cell Based Combined Heat and Power Systems. (February 2019) - Kwan, Trevor Hocksun; Yao, Qinghe
Abstract: Fuel cell based combined heat and power systems (FC-CHP) are a promising technology which can provide efficiently both electrical power and heat to residential and industrial consumers. However, FC-CHP system are typically complex in nature where much of the complexity arises from the necessary subsystems to operate the FC itself. This paper proposes a cost effective experimental emulator that acts like a real FC-CHP system by generating its key output characteristics while avoiding the complex component design of the real system. It achieves this by using two separate electrical circuits – One known as the Heat Emulator (HE) to emulate the waste heat characteristics and another, known as the Electric Power Emulator (EPE) to emulate the electrical power generation. Both circuits involve a controllable voltage source and a resistive load. A digital controller is then pre-programmed with an accurate FC model and its role is to control the source voltage and/or load resistance in the HE and EPE circuits such that these two circuits generate accurately the FC stack's output characteristics. The HE circuit and a liquid cooling system is specifically implemented and water temperature control is used to study this system's thermal efficiency.